2022
DOI: 10.15835/nbha50412859
|View full text |Cite
|
Sign up to set email alerts
|

Foliar spray of Si and Ti nanoparticles affected enzymatic antioxidants in rapeseed (Brassica napus L.)

Abstract: Some beneficial nanoparticles such as silicon and titanium are encouraging in foliar feeding due to their large surface area and biocompatible properties. In current experiment, seedling of rapeseed varieties (‘Hydromel’, ‘Nathalie’, ‘Alonso’) was sprayed with titanium dioxide and silicon dioxide nanoparticles (Ti and Si-NPs) and then responses of some enzymatic antioxidant and plasma membrane integrity were evaluated. Foliar application of Si-NPs significantly increased the activity of ascorbate peroxidase co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Zinc, as a cofactor of many key enzymes, regulates the biosynthesis of phytohormones such as auxin and abscisic acid. Silicon also plays a role as a beneficial element in stimulating defense and regulatory processes (Spalevic et al, 2022 ). Our findings are consistent with those of El-Zohri et al (2021), who reported that foliar spraying of green-synthesized Zn-NPs induced SOD, CAT, and APX activities, and reduced drought-induced oxidative stress, as indicated by the decreased levels of MDA and H 2 O 2 compared to untreated controls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zinc, as a cofactor of many key enzymes, regulates the biosynthesis of phytohormones such as auxin and abscisic acid. Silicon also plays a role as a beneficial element in stimulating defense and regulatory processes (Spalevic et al, 2022 ). Our findings are consistent with those of El-Zohri et al (2021), who reported that foliar spraying of green-synthesized Zn-NPs induced SOD, CAT, and APX activities, and reduced drought-induced oxidative stress, as indicated by the decreased levels of MDA and H 2 O 2 compared to untreated controls.…”
Section: Discussionmentioning
confidence: 99%
“…Karami et al (2016) observed increased activity of antioxidant enzymes, including superoxide dismutase, peroxidase, CAT, and proline, in soybeans following the foliar application of zinc under drought-stress conditions. Silicon, while nonessential for plant growth, has demonstrated beneficial effects when applied exogenously to various plant species (Liang et al, 2015; Spalevic et al, 2022 ). The application of silicon under drought stress conditions improves plant tolerance through multiple mechanisms, such as regulating aquaporin gene expression and reducing ROS, which inhibit aquaporin activity (Wang et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Over the last decade, a significant increase in the use of biostimulators has been observed in agricultural practice. In modern agriculture, foliar and soil application of nutrients is becoming a commonly used procedure (Kolarić et al 2021;Spalevic et al 2022), but both new and known preparations in agricultural practice should be tested under field experiments (Beres et al 2019, Rios et al 2019.…”
Section: Introductionmentioning
confidence: 99%